Non-Hodgkin lymphoma of the thyroid in a patient with hyperthyroidism. Issue 1 (2nd January 2021) - Lanham, Theresa; Lanham, Erik; Sullivan, Abigayle; Magaji, Vasudev
ABSTRACT: Primary thyroid lymphoma is incredibly rare with an annual incidence of approximately 2.1 per million persons, accounting for 2% of thyroid malignancies. One of the only known risk factors is autoimmune thyroid disease, specifically Hashimoto's, although there have been a few cases of thyroid lymphoma associated with Graves' disease. Here, we present one such case of a patient with pre-existing hyperthyroidism who developed non-Hodgkin's lymphoma of the thyroid. The patient initially presented with rapidly progressing right-sided neck swelling. He was clinically and biochemically euthyroid with negative thyroid stimulating immunoglobulin, maintained on methimazole. Biopsy of the thyroid nodule with flow cytometry revealed non-Hodgkin lymphoma. Intervention included radiation therapy.